2007
DOI: 10.1109/tbme.2006.880903
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Recording of Extracellular Potentials Produced by Microchannel-Confined Neurons In-Vitro

Abstract: Abstract-Towards establishing electrical interfaces with patterned in vitro neurons, we have previously described the fabrication of hybrid elastomer-glass devices polymer-on-multielectrode array technology and obtained single-electrode recordings of extracellular potentials from confined neurons (Claverol-Tinturé et al., 2005). Here, we demonstrate the feasibility of spatially localized multisite recordings from individual microchannel-guided neurites extending from microwell-confined somas with good signal-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
(28 reference statements)
1
31
0
Order By: Relevance
“…Nevertheless, the task of positioning a single neuron inside each micro-well of the pMEA is not straightforward. Neurons are usually loaded manually using glass micropipettes guided by micromanipulators (Maher et al, 1999;Suzuki et al, 2004;Claverol-Tinture et al, 2007), which is a time-consuming, workintensive procedure. Furthermore, the long period of time required for loading a few micro-wells could result in cells being damaged, which forbids the realisation of large-scale single-cell networks.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the task of positioning a single neuron inside each micro-well of the pMEA is not straightforward. Neurons are usually loaded manually using glass micropipettes guided by micromanipulators (Maher et al, 1999;Suzuki et al, 2004;Claverol-Tinture et al, 2007), which is a time-consuming, workintensive procedure. Furthermore, the long period of time required for loading a few micro-wells could result in cells being damaged, which forbids the realisation of large-scale single-cell networks.…”
Section: Introductionmentioning
confidence: 99%
“…7b, left) as demonstrated by various groups (Morin et al, 2005;Claverol-Tinture et al, 2007;Benmerah et al, 2009;Lacour et al, 2010). This would increase the likelihood of identifying the actual origin of the bioelectrical signals.…”
Section: Optional Strategies and Future Directionsmentioning
confidence: 92%
“…According to another research, signals collected from a MEA had typical amplitudes in the range of 20-600μV and the thermal noise ranged from 10μV to 20μV [12]. Claverol-Tinture et al [9] measured the extracellular potential of neurons with the open-well configuration. They found that some electrodes, although partially covered by the soma, remained electrically silent because the electrodes were grounded by the culture medium.…”
Section: Advances In Biological Sciences Research Volumementioning
confidence: 99%
“…Local cellular environment can be controlled at the micron scale by this approach, which is particularly useful in single-cell-based researches [7]. Techniques with chemically patterned growth substrates [8] or three-dimensional microstructures [9] were used successfully for cell patterning. Bani-Yaghoub et al [10] made specific topographic structures on polydimethylsiloxane (PDMS), and modified the property of PDMS surface with fluoroalkylsilane derivative solution to obtain a patterned neuronal network.…”
Section: Introductionmentioning
confidence: 99%